(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: The high neonatal mortality rate is still a major challenge facing Bangladesh. Identifying the predictors of mortality plays an important role in decreasing neonatal mortality. This study aimed to assess the mortality pattern and identify independent predictors of mortality among the neonates admitted to the Special Care Neonatal Unit (SCANU) of a tertiary hospital in Bangladesh. Materials and methods: This cross sectional study was conducted at the SCANU of Chittagong Medical College Hospital, including 6167 neonates admitted from July 2017 to December 2017. Predictors of mortality were determined by multivariate binary logistic regression analysis. Results: The neonatal case fatality rate was 21.4%. Major causes of death included perinatal asphyxia (39.4%), sepsis (26.6%) and respiratory distress syndrome (15.9%). Around 40% of neonates died within 24 hours of hospital admission. In the multivariate analysis, mortality was associated with age £1 day (Adjusted Odds Ratio [AOR]: 2.18; 95% CI: 1.70-2.78), referral from other districts of Chattogram division (AOR: 1.68; 95% CI: 1.37-2.06), out born babies delivered at other hospitals (AOR: 1.60; 95% CI: 1.35-1.89), and at home (AOR: 2.21, 95% CI: 1.75-2.80), vaginal delivery (AOR: 1.35; 95% CI: 1.151.59), preterm gestation (AOR: 3.80, 95% CI: 3.13-4.59) and weight at admission below 2500gm (AOR: 1.64; 95% CI: 1.37-1.95). Conclusions: Implementing a better referral link, delivery in a well-equipped hospital and timely intervention could decrease neonatal mortality in Chattogram, Bangladesh. JCMCTA 2024 ; 35 (2) : 28-34